Performance Analysis of A 3*2 MIMO System For Fading Channel (International Journal of Engineering and Computer Science, 2014)
This paper studies a multiple-input multiple-output (MIMO) wireless broadcast system along with its advantages and performance. Graphical representation and technical comparison between different input and output systems and other simulation results are presented.